Cortical trajectories during adolescence in preterm born teenagers with very low birthweight. (February 2016) - Rimol, Lars M.; Bjuland, Knut J.; Løhaugen, Gro C.C.; Martinussen, Marit; Evensen, Kari Anne I.; Indredavik, Marit S.; Brubakk, Ann-Mari; Eikenes, Live; Håberg, Asta K.; Skranes, Jon
Abstract: While cross-sectional neuroimaging studies on cortical development predict reductions in cortical volume (surface area and thickness) during adolescence, this is the first study to undertake a longitudinal assessment of cortical surface area changes across the continuous cortical surface during this period. We studied the developmental dynamics of cortical surface area and thickness in adolescents and young adults (aged 15–20) born with very low birth weight (VLBW; <1500 g) as well as in term-born controls. Previous studies have demonstrated brain structural abnormalities in cortical morphology, as well as long-term motor, cognitive and behavioral impairments, in adolescents and young adults with VLBW, but the developmental dynamics throughout adolescence have not been fully explored. T1-weighted MRI scans from 51 VLBW (27 scanned twice) and 79 term-born adolescents (37 scanned twice) were used to reconstruct the cortical surface and produce longitudinal estimates of cortical surface area and cortical thickness. Linear mixed model analyses were performed, and the main effects of time and group, as well as time × group interaction effects, were investigated. In both groups, cortical surface area decreased up to 5% in some regions, and cortical thickness up to 8%, over the five-year period. The most affected regions were located on the lateral aspect of the hemispheres, in posterior temporal, parietal and to some extent frontal regions. There was no significant interaction between time and group for either morphometry variable. In conclusion, cortical thickness decreases from 15 to 20 years of age, in a similar fashion in the clinical and control groups. Moreover, we show for the first time that developmental trajectories of cortical surface area in preterm and term-born adolescents do not diverge during adolescence.